Modeling climatic suitable areas for kedondong (Spondias dulcis) cultivation in central part of Sumatra, Indonesia - Ibna Hayati; Alex Hartana; Nina Ratna Djuita (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Hayati I, Hartana A, Djuita NR. 2019. Modeling climatic suitable areas for kedondong (Spondias dulcis) cultivation in central part of Sumatra, Indonesia. Biodiversitas 20: 3608-3618. Kedondong (Spondias dulcis Parkinson) is a fruit plant native to Society Island (Polynesia, Pacific Islands) and widely cultivated in many tropical regions and countries. However, little is known about the occurrences and potential distribution of kedondong as well as its adaptability to different climate particularly in central part Sumatra. This paper is the first to predict the distribution of kedondong in central part of Sumatra in spatially explicit way. The maximum entropy (MaxEnt) model was used to analyze the geographical distribution of kedondong and to map its climatically suitable habitat in central part of Sumatra. The results showed that the MaxEnt model can be used to predict the climatic suitable areas for kedondong cultivation. Notably, the extent of the potentially suitable habitat was significantly larger than the present occurrence of kedondong in central part of Sumatra. The most suitable areas identified in this study covered the west coast of Sumatra and the central part of Sumatra but did not reach the eastern coast. They included parts of Kuantan Singingi, Indragiri Hulu, Indragiri Hilir and Pelalawan of Riau Provinces, Batang Hari of Jambi Provinces, and western part which include Agam, Tanah Datar, West Pasaman, Limapuluh Kota, Padang Pariaman, Padang and South Pesisir of West Sumatra Provinces. The MaxEnt model performed better than random method with an Area Under Curve (AUC) value of 0.981. Although kedondong is still largely ignored by scientific community and its potential has not been deeply explored, the findings of this study imply that it is very important to develop kedondong germplasm resources which have adaptability to extreme climate in central part of Sumatra.